Испытания устойчивости калькулятора к воздействию ЭМИ наносекундного диапазона - Князев, Владимир Владимирович; Иванов, Владимир Михайлович; Танцура, Александр Иванович (НТУ "ХПИ", 2017)
Представлены результаты испытаний устойчивости электронного калькулятора к воздействию электромагнитного импульса с параметрами, соответствующими требованиям MIL-STD-461G (процедура RS105). Испытания проведены с использованием технического обеспечения Эталона единиц сильных импульсных электрических и магнитных полей. Результаты испытаний показали, что уже при напряженности электрического поля ЭМИ равной 17,7 кВ/м проявляется эффект обнуления информации на экране калькулятора.

Results of tests for immunity of electronic calculator to action of electromagnetic pulse with parameters corresponding to the requirements of MIL-STD-461G (procedure RS105) are presented. The tests were carried out with use of hardware of the Primary standard of units of strong pulsed electric and magnetic fields. For this purpose, additionally, the generator of EMP supplying the specified amplitude-time parameters of a pulse, connected in the system of the Primary standard of REMP instead of the generator of exponential pulses, was made. The results of the tests showed that effect of nulling of information at the calculator screen takes place already at electric field strength of EMP of 17,7 kV/m, but its serviceability remains intact. When electric field was 35.2 kV/m serviceability of the calculator was broken (the screen went out, without possibility to recover serviceability by «turn on-turn off» operation). Analysis showed that the failure was caused by degradation of the controller
A practical example of determination of immunity of equipment to action of EMP of nanosecond range
Keywords: электромагнитный импульс; электронный калькулятор; генератор ЭМИ; полеобразующая система; деградация контролера; immunity; electromagnetic pulse; electronic calculator; generator of EMP